2019
DOI: 10.15171/bi.2020.04
|View full text |Cite
|
Sign up to set email alerts
|

PEGylated gold nanoparticles-ribonuclease induced oxidative stress and apoptosis in colorectal cancer cells

Abstract: <span style="color: #1f497d;">Introduction: Currently, drug-induced reactive oxygen species (ROS) mediating apoptosis pathway have extensively been investigated in designing effective strategies for colorectal cancer (CRC) chemotherapy. Bovine pancreatic ribonuclease A (RNase A) represents a new class of cytotoxic and non-mutagenic enzymes, and has gained more attention as a potential anticancer modality; however, the cytosolic ribonuclease inhibitors (RIs) restrict the clinical application of this enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…The plasmon absorption maximum shifted to a higher wavelength due to higher oscillation modes. Hence, this result clearly indicates that the respective particles became larger when the PEGylation steps were repeated. , Previous studies showed that a slight red shift of the absorption spectrum (5–6 nm) appeared when the diameter of AuNPs increased by approximately 10 nm upon pegylation. Raman spectroscopy also confirmed the presence of PEG moieties on the surface; AuNP@PEG exhibited two distinctive bands at approximately 1150 cm –1 (C–C stretching) and 1495 cm –1 (CH 2 –CH 2 bending) (Figure b) . Thus, based on these spectroscopic analysis results, we concluded that AuNPs were successfully decorated with two PEG chains by confirming the red shift and presence of PEG moieties in AuNP@PEG.…”
Section: Resultssupporting
confidence: 66%
“…The plasmon absorption maximum shifted to a higher wavelength due to higher oscillation modes. Hence, this result clearly indicates that the respective particles became larger when the PEGylation steps were repeated. , Previous studies showed that a slight red shift of the absorption spectrum (5–6 nm) appeared when the diameter of AuNPs increased by approximately 10 nm upon pegylation. Raman spectroscopy also confirmed the presence of PEG moieties on the surface; AuNP@PEG exhibited two distinctive bands at approximately 1150 cm –1 (C–C stretching) and 1495 cm –1 (CH 2 –CH 2 bending) (Figure b) . Thus, based on these spectroscopic analysis results, we concluded that AuNPs were successfully decorated with two PEG chains by confirming the red shift and presence of PEG moieties in AuNP@PEG.…”
Section: Resultssupporting
confidence: 66%
“…Treatment with AuNPs-RNase-PEG showed a cytotoxic effect mainly associated with chromatin condensation and nuclear fragmentation, eventually leading to apoptosis. In addition, increased levels of ROS were detected, suggesting that there is a correlation between the production of ROS and the induction of apoptosis [ 46 ]. Antibody-based therapy for malignant tumors has recently increased.…”
Section: Metallic Nanoparticlesmentioning
confidence: 99%
“…In this sense, Khiavi (2020) synthesized AuNPs and functionalized them with RNase A and stabilized them with polyethylene glycol (PEG) (AuNPs-RNase-PEG) and then investigated their effect on colon cancer cells (SW-480), treatment with AuNPs-RNase-PEG showed a cytotoxic effect mainly associated with chromatin condensation and nuclear fragmentation, eventually leading to apoptosis. In addition, increased levels of ROS were detected, suggesting that there is a correlation between the production of ROS and the induction of apoptosis [40]. Antibody-based therapy for malignant tumors has recently increased.…”
Section: Gold Nanoparticlesmentioning
confidence: 99%